2023
DOI: 10.1007/s00268-023-07029-x
|View full text |Cite
|
Sign up to set email alerts
|

Are LMICs Achieving the Lancet Commission Global Benchmark for Surgical Volumes? A Systematic Review

Abstract: Introduction The Lancet Commission on Global Surgery (LCoGS) set the benchmark of 5000 procedures per 100,000 population annually to meet surgical needs adequately. This systematic review provides an overview of the last ten years of surgical volumes in Low and Middle- Income-Countries (LMICs). Methodology We searched PubMed, Web of Science, Scopus, Cochrane, and EMBASE databases for studies from LMICs addressing surgical volume. The number of surgeries pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Patil et al’s (2023) systematic review found that in LMICs, an average of 877 surgeries per 100,000 population increased with gross domestic product per capita. India and Brazil reported volumes close to the LCoGS benchmark (Patil et al 2023 ). The study suggests that weak healthcare infrastructure, rising medical supply and equipment costs, supply chain disruptions, and health system issues may contribute to low surgical productivity and income levels.…”
Section: Discussionmentioning
confidence: 97%
“…Patil et al’s (2023) systematic review found that in LMICs, an average of 877 surgeries per 100,000 population increased with gross domestic product per capita. India and Brazil reported volumes close to the LCoGS benchmark (Patil et al 2023 ). The study suggests that weak healthcare infrastructure, rising medical supply and equipment costs, supply chain disruptions, and health system issues may contribute to low surgical productivity and income levels.…”
Section: Discussionmentioning
confidence: 97%
“…We would like to thank Siddhesh Zadey for reading our article with great interest; however, we disagree with Zadey [1] and take this opportunity to provide further information on our systematic review [2].…”
Section: Dear Editormentioning
confidence: 96%
“…A systematic review of surgical volumes across LMICs found substantial heterogeneity in data collection, including inconsistencies in the nomenclature and definitions of surgeries, and variations in methods used to measure surgical volumes. 24 Whereas the Lancet Commission 2020 listed postoperative mortality rate (POMR) as one of the six key indicators for safe surgery, a review of the published literature of POMR reporting from LMICs showed multiple limitations such as unclear outcome definitions, inconsistent timeframes for outcome reporting and variable denominators for number of surgeries, with studies from upper MICs having more precise reporting than lower MICs or LICs. 25 Another study looking at morbidity after surgical management of cervical cancer found that reliable, high-quality data was not available for the majority of LICs where cervical cancer is highly prevalent.…”
Section: Problems With Routine Health Information Datamentioning
confidence: 99%
“…Many LMICs lack the resources needed to collect routine information on health‐related services and activities, resulting in inadequate information on baseline health indicators and dearth of basic quality assurance systems. A systematic review of surgical volumes across LMICs found substantial heterogeneity in data collection, including inconsistencies in the nomenclature and definitions of surgeries, and variations in methods used to measure surgical volumes 24 . Whereas the Lancet Commission 2020 listed postoperative mortality rate (POMR) as one of the six key indicators for safe surgery, a review of the published literature of POMR reporting from LMICs showed multiple limitations such as unclear outcome definitions, inconsistent timeframes for outcome reporting and variable denominators for number of surgeries, with studies from upper MICs having more precise reporting than lower MICs or LICs 25 .…”
Section: Problems With Routine Health Information Datamentioning
confidence: 99%